“Permita que eu fale, não as minhas cicatrizes” : teoria e música em Beyoncé e Emicida - Mariana Sales de Abreu (2022)
This thesis investigates the epistemic resources employed by black artists to produce critical intellectual discourses through music. Considering that the arts have been used by Black people historically as a site of education and resistance, it is possible to understand that musical language offers specific affordances to construct its messages using internal and external dialogues in social communities. This text has intersectionality as a background, paying attention to the manners how different articulated power axis influence the artists’ work. The debates concerning the margins as a location of creativity and struggle for justice are used as an additional background. The analytical corpus is composed by four albums: Sobre Crianças, Quadris, Pesadelos e Lições de Casa [2015] and AmarElo [2019], by Emicida, and Lemonade [2016] and The Gift [2020], by Beyoncé. Through them, a Critical Discourse Analysis was conducted taking into consideration elements such as the use of samples, the combination of musical genres, featured participations, the employment of pretuguês and Black English, amongst others. These resources help to understand how dialogues between social groups and contexts are established. Furthermore, the thesis observes the elaboration of interpretations, theorizations and criticisms through music, centralizing the themes of family, affects, community and resistance.